Layered topological semimetal GaGeTe: New polytype with non-centrosymmetric structure - Gallego-Parra, S; Bandiello, E; Liang, A; da Silva, E. Lora; Rodriguez-Hernandez, P; Munoz, A; Radescu, S; Romero, A. H; Drašar, Čestmír; Errandonea, D; Manjon, F. J (Elsevier Science BV, 2022)
GaGeTe is a layered van der Waals material composed of germanene and GaTe sublayers that has been recently predicted to be a basic Z2 topological semimetal. To date, only one polytype of GaGeTe is known with trigonal centrosymmetric structure (a phase, space group R-3m, No. 166). Here we show that asgrown samples of GaGeTe show traces of at least another polytype with hexagonal noncentrosymmetric structure (f3 phase, space group P63mc, No. 186). Moreover, we suggest that another bulk hexagonal polytype (g phase, space group P-3m1, No. 164) could also be found near room conditions. Both a and f3 polytypes have been identified and characterized by means of X-ray diffraction and Raman scattering measurements with the support of ab initio calculations. We provide the vibrational properties of both polytypes and show that the Raman spectrum reported for GaGeTe almost forty years ago and attributed to the a phase, was, in fact, that of the secondary f3 phase. Additionally, we show that a Fermi resonance occurs in a-GaGeTe under non-resonant excitation conditions, but not under resonant excitation conditions. Theoretical calculations show that bulk f3-GaGeTe is a non-centrosymmetric weak topological semimetal with even smaller lattice thermal conductivity than centrosymmetric bulk aGaGeTe. In perspective, our work paves the way for the control and engineering of GaGeTe polytypes to design and implement complex van der Waals heterostructures formed by a combination of centrosymmetric and non-centrosymmetric layers of up to three different polytypes in a single material, suitable for a number of fundamental studies and technological applications. (c) 2022 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Vrstevnatý topologický polokov GaGeTe: Nový polytyp s necentrosymetrickou strukturou
Keywords: GaGeTe; topological semimetal; non-inversion symmetry; GaGeTe; topologický polokov; absence inverzní symetrie